REVOLUTIONIZING RECRUITMENT: THE ROLE OF ARTIFICIAL INTELLIGENCE IN TALENT ACQUISITION - Raji N; George, Valsa; Iyer, Radhieka S; Sharma, Suhani; Pathan, Firozkhan I; Basha S, Mahabub (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancements in Artificial Intelligence (AI) are transforming various sectors, and talent acquisition is no exception. This research paper exploring how AI-driven tools are reshaping the way organizations attract, evaluate, and hire talent. With the global competition for top talent intensifying, the need for efficient, data-driven hiring strategies is critical. AI technologies, including machine learning, natural language processing, and predictive analytics, have become pivotal in streamlining tasks such as resume screening, candidate matching, and interview scheduling, significantly reducing time-to-hire and improving candidate experiences. This paper conducts a thorough analysis of AI’s integration into talent acquisition, AI’s benefits, challenges, and ethical considerations. Key findings show that AI reduces hiring time by up to 50%, enhances candidate engagement through automation, and allows for more informed hiring decisions. Despite its potential, organizations must carefully manage the ethical challenges AI poses to ensure fair and transparent recruitment practices. In conclusion, AI has the potential to revolutionize talent acquisition, but its success depends on thoughtful implementation and continuous evaluation to mitigate risks and maximize benefits.